Między paradygmatami. Problemy terminologiczne w przekładzie ofert nieruchomości - Walkiewicz, Barbara (Investigationes Linguisticae, 2019)
The aim of this paper is to present problems translating real estate terms into French. The author analyses translations of real estate with regard to the translator’s terminological precision and its impact on the retention of the basic functions of the original.